P-487 Development of an educational portal of in vitro fertilization with donated oocytes. (30th June 2022) - Robin, F; Leal, S M C; Zocche, D A D A; Andrade, G; Frantz, N
Abstract: Study question: What are the needs related to facing the diagnosis and treatment of in vitro fertilization with donated oocytes? Summary answer: The scarcity of clinical case reports on egg donation treatments makes acceptance difficult, highlighting the importance of an educational portal focused on the topic. What is known already: It is known that in vitro fertilization with donated oocytes is a solitary treatment, since the vast majority of people who undergo do not tell friends and family about it. In addition, it is a treatment that can exacerbate different feelings such as sadness, shame of friends and family, feelings of incapacity, among others. Thus, it is known that the little information combined with the difficulty of accepting this new possibility makes it difficult for patients to engage in treatment. Study design, size, duration: A methodological study divided into three stages was carried out: 1) descriptive quantitative study with a total of 222 participants; 2) qualitative study with a total of 22 participants; 3) construction and validation of the educational portal with health judges. Data were collected between January 2017 and April 2020. The collection, data analysis, construction and validation of the educational portal took a period of two years. Participants/materials, setting, methods: Participants women and heterosexual couples undergoing IVF treatment with donated oocytes. Quantitative research: through information from the database of the clinic under study. Qualitative research: sending an electronic questionnaire to selected participants. The construction of the educational portal: from the data collected in the qualitative research. The validation of the educational portal: the content was by seven health judges and the quality of the tool through the google lighthouse program. Main results and the role of chance: The quantitative research identified the profile of patients, 37% are between 40 and 44 years old, 79% had a diagnosis of ovarian failure and in 84% and 81% of the participants received fresh eggs and did not undergo preimplantation genetic testing, respectively. Regarding qualitative studies, it was possible to confirm the feeling of lack of information and lack of knowledge about the egg donation theme, in 100% of the reports. In addition, patients commented about many different feelings experienced during treatment, in addition to the lack of contact with people who had already been through the same situation. Based on these reports, it was possible to identify the patients' needs for information/support and to develop an educational portal where it was possible to find up-to-date articles, local legislation, listen and read testimonies from patients who have gone through all stages of the process. After the construction of the educational portal, the content validation index was 1, in the categories: objectives, structure and presentation and relevance. All stages of the study were carried out so that the future patient has a good experience when accessing the site, promoting the promotion of knowledge and being a facilitator in the acceptance of knowledge. Limitations, reasons for caution: The survey of cases, as well as the needs of the patient, took place within the units of the same clinic, limiting the population studied. The qualitative stage was carried out only with couples who were pregnant or had already given birth due to the delicacy of the topic. Wider implications of the findings: As it is the first educational portal on egg donation in Brazil, it has potential facilitated through the promotion of knowledge to couples who need to use the technique of in vitro fertilization with donated oocytes and to all those interested in the subject. Trial registration number: Não aplicável